Analysis and occurrence of some phenol endocrine disruptors in two marine sites of the northern coast of Sicily (Italy). Issue 1 (15th July 2017) - Errico, Sonia; Nicolucci, Carla; Migliaccio, Marina; Micale, Valeria; Mita, Damiano G.; Diano, Nadia
Abstract: This study reports the occurrence of some endocrine disrupting chemicals in red mullet samples and sediments collected in two representative sites of the northern Sicilian coast (Italy). For this purpose, an improved method, using solid extraction and high-performance liquid chromatography analyses for the simultaneous determination of bisphenol A (BPA), 4-nonylphenol (4-NP) and 4-t-octylphenol (4-t-OP) in fish tissues and sediments, has been developed and validated. Method performance was demonstrated over the concentration range 0.1–200 ng/mL, with detection limits from 0.06 to 0.1 ng/mL. Recoveries ranged from 83.4% to 102.6%, with relative standard deviations of 7.7–14.0% for the entire procedure. Results showed that BPA, 4-t-OP and 4-NP were detected in all fish samples and sediments from two sampling sites, indicating that these chemicals have contaminated Mediterranean aquatic ecosystem and have accumulated in fish. The study provided more comprehensive fundamental data for risk assessment and contamination control of phenolic EDCs in aquatic environment. Highlights: A HPLC-FLD method for bisphenol A, 4-nonylphenol, 4-t-octylphenol levels in fish tissues is proposed. The method was in-house validated, and is sensitive, accurate and precise. Liver and muscle of red mullets from two sites along the northern coast of Sicily have been analyzed. BPA, 4-t-OP and 4-NP were detected in all fish samples at two sampling sites. These chemicals have contaminated Mediterranean aquatic ecosystem and have accumulated in fish.